Integrasi Nilai-Nilai Piil Pesenggiri sebagai Kearifan Lokal dalam Pembentukan Karakter Peserta Didik di Lampung - Muarafa Nur Afif; Novri Rahman (Advances In Education Journal, 2025)
This study aims to analyze the integration of Piil Pesenggiri values ​​as local wisdom in character formation for students in Lampung Province. The approach used is descriptive qualitative, with analysis based on literature review and ethnography of cultural education. This approach allows for a deeper understanding of the philosophical, social, and pedagogical dimensions embodied in Piil Pesenggiri values ​​and their relevance to character education. The analysis was conducted using Braun and Clarke's thematic analysis model to identify four core values: nemui nyimah (friendliness and social empathy), nengah nyappur (ethics of social interaction), sakai sambayan (mutual cooperation and solidarity), and juluk adok (honor and moral integrity). The results indicate that these values ​​can serve as both a philosophical and pedagogical foundation for character formation for students through habituation, role modeling, and internalization of local cultural values. Thus, Piil Pesenggiri functions not only as a cultural identity for the Lampung community but also as a source of moral values ​​for strengthening the nation's character.